The effects of corruption on Peru's economic growth during the period 1998-2018 - Benito Marro, Stephany Alessandra (2021)
The objective of this research was to determine the effect of corruption on economic growth in Peru for the period 1998-2018. It was determined how economic growth was affected both in the short and long term by corruption. The corruption control index was used to measure corruption and the variation in gross domestic product (GDP) at constant prices was used to measure economic growth. To determine this effect, the hypothetical deductive method was used as a general method since we sought to corroborate a hypothesis and as a specific method, we used the Autoregressive Model of Distributed Lag (ARDL) since this model adapts well to small samples, likewise we had a non- experimental research design – longitudinal explanatory. Data were collected from the World Bank and the Ministry of Education (MINEDU) from 1998 to 2018. As a result of the econometric ARDL model, it was obtained that corruption had a negative effect on economic growth since an improve- ment of one percentage point in the corruption index would mean an improvement of 0.55 percent- age points in economic growth. Therefore, it is concluded that the effect of corruption has a negative effect on economic growth as expected according to the reviewed antecedents.